Removal of Fluoride from Drinking Water Using Modified Immobilized Activated Alumina. (30th October 2012) - Rafique, Aneeza; Awan, M. Ali; Wasti, Ayesha; Qazi, Ishtiaq A.; Arshad, Muhammad
Abstract : The study describes the removal of fluoride from drinking water using modified immobilized activated alumina (MIAA) prepared by sol-gel method. The modification was done by adding a specific amount of alum during the sol formation step. The fluoride removal efficiency of MIAA was 1.35 times higher as compared to normal immobilized activated alumina. A batch adsorption study was performed as a function of adsorbent dose, contact time, stirring rate, and initial fluoride concentration. More than 90% removal of fluoride was achieved within 60 minutes of contact time. The adsorption potential of MIAA was compared with activated charcoal which showed that the removal efficiency was about 10% more than the activated charcoal. Both the Langmuir and Freundlich adsorption isotherms fitted well for the fluoride adsorption on MIAA with the regression coefficient R 2 of 0.99 and 0.98, respectively. MIAA can both be regenerated thermally and chemically. Adsorption experiments using MIAA were employed on real drinking water samples from a fluoride affected area. The study showed that modified immobilized activated alumina is an effective adsorbent for fluoride removal.